Konstitusionalitas Pemindahan Ibu Kota Negara dalam Perspektif Living Constitution: Analisis Putusan Mahkamah Konstitusi Nomor 34/PUUXX/2022 dan Implikasinya terhadap Pembangunan Berkelanjutan - Exsyel Hendy Basuki; Windya Nopryanti; Khoirul Abdul Aziz; Ilham Muhammad Zain; Hezron Sabar Rotua Tinambunan; Febrian Indar Surya Kusuma (Jurnal Hukum Lex Generalis, 2026)
The relocation of Indonesia's capital city to Ibu Kota Nusantara through Law Number 3 of 2022 triggered the largest wave of judicial review in Indonesian constitutional history. This article analyzes the constitutionality of this policy through the lens of living constitution theory, focusing on the ratio decidendi of Constitutional Court Decision Number 34/PUU-XX/2022. Using normative legal research with statutory, case and conceptual approaches, it finds that the Court employed judicial restraint via the open legal policy doctrine, yet applied the meaningful participation parameter inconsistently compared to Decision Number 91/PUU-XVIII/2020. The ruling carries ambivalent implications for SDG 11 and SDG 16.